2023
DOI: 10.1097/txd.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Impact of Insurance Type on Kidney Transplant Waitlist Status and Posttransplantation Outcomes in the United States After Implementation of the Affordable Care Act

Abstract: Background. Insurance type, a marker of socioeconomic status, has been associated with poor access to kidney transplant (KT) and worse KT outcomes before the implementation of the Affordable Care Act (ACA) and the revised Kidney Allocation System (KAS). In this study, we assessed if insurance type remained a risk marker for worse waitlist and transplant outcomes after ACA and KAS. Methods. Using Scientific Registry of Transplant Recipients data, we assessed insurance type of waitlisted candidates pre- (2008–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Additionally, in a systematic review conducted by Lu et al [14], several studies revealed structural racism and biases, which include racial profiling by clinicians and providers, and social determinants of health, such as poor neighborhoods and built environmental conditions, contributed to lower access to kidney transplantation among Black patients. Across studies, various socioeconomic variables, such as low income, neighborhood poverty, publicly funded insurance, limited levels of knowledge regarding the transplantation process, and logistical issues, such as lack of transportation and far distance to transplant centers, have consistently been associated with disparities in access to transplant in the Black population, despite Black patients demonstrating more serious disease status compared to White patients [15][16][17][18][19][20].…”
Section: Waitlist Access Disparitiesmentioning
confidence: 99%
“…Additionally, in a systematic review conducted by Lu et al [14], several studies revealed structural racism and biases, which include racial profiling by clinicians and providers, and social determinants of health, such as poor neighborhoods and built environmental conditions, contributed to lower access to kidney transplantation among Black patients. Across studies, various socioeconomic variables, such as low income, neighborhood poverty, publicly funded insurance, limited levels of knowledge regarding the transplantation process, and logistical issues, such as lack of transportation and far distance to transplant centers, have consistently been associated with disparities in access to transplant in the Black population, despite Black patients demonstrating more serious disease status compared to White patients [15][16][17][18][19][20].…”
Section: Waitlist Access Disparitiesmentioning
confidence: 99%